Pemberdayaan Kelompok Peternak Sapi Perah Margo Mulyo Melalui Pelatihan Peningkatan Nilai Produk Olahan Susu - Lina Rifda Naufalin; Aldila Dinanti; Arif Kelik Nugroho (Universitas Muhammadiyah Parepare)
The purpose of this community service activity is to help the cattle rancher group "Margo Mulyo" in increasing the value of its products so that the group's income and prosperity increase. Specifically, the main objectives of this training, namely (1) Increasing the value of products that have been produced, (2) Increasing the attractiveness of the product, (3) Increasing the level of product sales, (4) Improving the ability of group administration and financial records. The stages in this service activity include the planning phase and the implementation phase. The stages of planning are meeting with partners, identifying problems, coordinating with experts/resource persons and arranging schedules for the implementation of training. The implementation phase consists of Branding and Packaging training, product photo training using the Snapseed application, e-commerce training, marketing assistance through e-commerce, and financial administration and records training. Output targets are partners having attractive product photos to market, more attractive product packaging, having brands that are of interest in buying, partners can market products online, and partners having administrative books and cash books as needed. Partners feel that this training is very effective because it is easy to apply and under the technology they need.